PEMANFAATAN MEDIA PEMBELAJARAN VIDEO YOUTUBE DALAM MENINGKATKAN MOTIVASI BELAJAR STATISTIK INFERENSIAL PENDIDIKAN EKONOMI - Tutfi Dwi Febrianti; Witarsa Witarsa; Husni Syahrudin (Universitas Tanjungpura, 2022)
This research was conducted at the Economic Education Study Program, Faculty of Teacher Training and Education, Tanjungpura University, Pontianak. The purpose of this study was to determine the use of YouTube in increasing motivation to learn inferential statistics for the economic education study program FKIP Untan seen from the use of YouTube, student learning motivation, and the advantages and disadvantages of using YouTube. This type of research approach is a qualitative approach with a descriptive method. There were 6 informants, of which 5 were students and 1 was a lecturer in inferential statistics. Data collection techniques with interviews and direct observation. Based on the research it was found that: 1) the use of YouTube was used in 2020, the amount of time students watched YouTube in a day was an average of 4-6 hours, the duration of videos used in learning was 12-14 minutes, and students liked videos. YouTube is used in the learning process because the explanations are easy to understand and can be used as examples in doing assignments; 2) students' learning motivation can be seen from: a) their desire to graduate, b) enthusiasm for learning and doing assignments, c) being able to answer questions during the question and answer session; 3) the advantages are shown in: quickly understanding the material, the disadvantages are on the internet network and internet quota, and the difficulty in conducting direct questions and answers.